Distribution of Royalties for Songs Created by Husband After Divorce - Latusawaule, Jilly Sekale; Latupono, Barzah; Labetubun, Muchtar Anshary Hamid (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study analyzes the distribution of royalties on songs created by husbands after divorce as a form of joint property in marriage. This issue is significant in Indonesia, considering that royalties are included as Intellectual Property Rights that can provide economic value for divorced couples, but are not yet fully protected and often trigger legal disputes.Purposes of the Research: This study aims to explain the mechanism for the distribution of royalties from songs created by a husband after divorce as joint property and the legal consequences for wives who do not receive these royalties.Methods of the Research: This study uses a normative legal research method with a statutory and conceptual approach. The analysis was conducted based on Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 concerning Marriage, Law Number 28 of 2014 concerning Copyright, and Government Regulation Number 56 of 2021 concerning the management of royalties for song and/or music creations.Findings of the Research: The results of this study reveal that royalties for songs created by the husband obtained during the marriage are included in joint assets that must be divided fairly in accordance with Article 35 and Article 37 of the Marriage Law. A wife who does not receive her share can file a lawsuit to obtain legal protection for the royalties. This division can also be carried out through deliberation, mediation, or court decisions to ensure justice for both parties.